ANALISA PENGARUH JUMLAH LILITAN DAN DIAMETER TEMBAGA PADA TRAFO TERHADAP DAYA OUTPUT MESIN SPOT WELDER AND SOLDERING IRON SEMI PORTABLE - Sedjati, Moch. Ari Wibowo; Wulandari, Diah (Jurnal Rekayasa Mesin, 2022)
In the welding process, there are still some obstacles, namely the welding equipment used still requires a large amount of electricity. For this reason, a welding tool that has relatively small electrical power is needed, it requires a transformer that is able to cut electrical power. To answer the above problems, the author is interested in developing a MOT (Microwave Oven Transformer) transformer whose secondary winding is modified as an alternative to conventional transformers so that the electric power becomes small. This plan aims to make a transformer with an output power of 450 Watt on a "semi-portable spot welder and soldering iron machine" and capable of operating at home with 450 VA electricity. The process of making a transformer begins with determining the output power generated by a MOT (Microwave Oven Transformer) transformer. The design method determines the number of turns and the diameter of the copper in the transformer by using copper with a diameter of 12 mm and 16 mm, while the work concept determines the basic concept of calculating the output power and efficiency of the MOT (Microwave Oven Transformer) transformer.